Organizational and Managerial Barriers in Humanitarian Organisations in Jordan - Raeda Saada; Taghrid Suifan (International Journal of Supply Chain Management, 2020)
Information sharing is the act of exchanging data between numerous humanitarian organizations, individuals and technologies in order to ascertain that the context of supply chain management is achieved. Information sharing within humanitarian supply chain organizations is paramount as it ascertains that strategic planning and decision making brings forth a timely and better response to affected humanitarian individuals. The process of information sharing within the humanitarian organizations is encouraged because it leads to an increase in performance at a reduced cost across the supply chain. The article explored information sharing barriers in humanitarian organizations, by specifically focusing on the organizational and managerial departments in the supply chain process of information sharing. To gain an understanding on information sharing within the humanitarian supply chain organization (HSCO), use of case studies that incorporated interviews brought out what was needed. The methodology used the induction approach in the research design because focused on human aspects, understanding the research context, gathering qualitative data and flexibility to change the structure of the research during the research stages. The population of the study were humanitarian organizations in Jordan. Sampling consisted of searching from different websites, forums, and the ministry of planning and International Corporation. The analysis and result part indicated that the interviews conducted from the case studies were similar in result. The result was similar because the barriers identified were similar. For instance, the notable barriers were lack of trust, security of information and skills and capacity building. The paper summed up that barriers like lack of trust and lack of knowledge within organizational structure are likely to affect the effectiveness of information sharing in humanitarian organizations in Jordan.